ARTIFICIAL INTELLIGENCE IN MARKETING AS A NEW CONCEPT AND BUSINESS OPPORTUNITY FOR INCREASING THE EFFICIENCY OF COMPANIES - Suyunova Kamilla Baxromovna; Tulanboyev Akbarjon; Tokhirov Abdulatif (Web of Journals Publishing, 2025)
The research paper examines the possibility of using artificial intelligence in the marketing activities of a company. Artificial intelligence in marketing is presented as a new concept and business opportunity to improve the efficiency of companies. Artificial intelligence can analyze user data to determine the profile of the target audience, identify customer preferences and study consumer behavior. The obtained data will help marketing specialists to offer effective and profitable strategies. The use of artificial intelligence will personalize customer needs and create a high-quality contingent in business. Customer data analysis improves the quality behavioral recommendations and will help to build market trends. The purpose of this study is to create a concept for the use of artificial intelligence in the marketing activities of companies to improve the effectiveness of key performance indicators of companies. Research objectives: to consider the elements of marketing with artificial intelligence, to find out the degree of its influence on the effectiveness of key performance indicators of companies; to develop a concept for the use of artificial intelligence in marketing. The following methods were used in the study: the method of analysis, the method of description and comparison. The scientific article used the following approaches to research and study of the material: scientific, systemic, innovative. As a result of the study, the authors proposed the structure of the concept of using artificial intelligence in marketing to improve the effectiveness of economic, technical, and environmental indicators of companies.
Keywords: Artificial intelligence; efficiency; competitiveness; concept; business opportunity; marketing.